Mengembangkan Kreativitas dalam Berpikir Melalui Pengajaran Sains (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 1993)
This article provide{views on different approach in science teaching which can develop creative thinking in the approach apply (1) system apporach. (21 problem solving strategy and (3) science process skill approaches and supported by creative teacher with open heart, not frighten but able to make students find themselves will and able to modify and develop subject matter. By developing, thinking creatively in science teaching, is hoped that students are able (1) to solve problems using alternative ways, and (2) to decide causal relation about objects observed.